Changes in the Eurozone governance after the crisis and the issue of growth - Schilirò, Daniele (Munich, 2013)
"The Eurozone countries are still trying to find a way out to the crisis that has affected the European Monetary Union (EMU) since 2010. Sovereign debt crisis, difficulties in the banking system and large current account imbalances have characterized the crisis of the euro, while several countries of Eurozone have entered in a phase of slow and even negative growth. All this have put at risk the sustainability of EMU, leading to a climate of pessimism and distrust about the future of the single currency. The crisis of the Eurozone has shown that a sustainable currency union requires more governance because of the higher degree of economic, financial and fiscal spillovers between euro member countries. However, the crisis has led to significant changes in the institutional framework of EMU and in the economic policies of Eurozone, highlighting above all the role of ECB. The present contribution analyzes these changes in the eurozone governance and discusses whether they are the correct solutions to the crisis, it also focuses on the unresolved issue of growth in the peripheral Eurozone countries."